Malaria control along China-Myanmar Border during 2007–2013: an integrated impact evaluation. Issue 1 (December 2016) - Xu, Jian-Wei; Li, Yong; Yang, Heng-Lin; Zhang, Jun; Zhang, Zai-Xing; Yang, Ya-Ming; Zhou, Hong-Ning; Havumaki, Joshua; Li, Hua-Xian; Liu, Hui; Zhou, Hua; Xie, Xin-Yu; et al.
Abstract Background Implementing effective interventions remain a lot of difficulties along all border regions. The emergence of artemisinin resistance ofPlasmodium falciparum strains in the Greater Mekong Subregion is a matter of great concern. China has effectively controlled cross-border transmission of malaria and artemisinin resistance ofP. falciparum along the China-Myanmar border. Methods A combined quantitative and qualitative study was used to collect data, and then an integrated impact evaluation was conducted to malaria control along the China-Myanmar border during 2007–2013. Results The parasite prevalence rate (PPR) in the five special regions of Myanmar was decreased from 13.6 % in March 2008 to 1.5 % in November 2013. Compared with the baseline (PPR in March 2008), the risk ratio was only 0.11 [95 % confidence interval (CI ), 0.09–0. 14) in November 2013, which is equal to an 89 % reduction in the malaria burden. Annual parasite incidence (API) across 19 Chinese border counties was reduced from 19.6 per 10 000 person-years in 2006 to 0.9 per 10 000 person-years in 2013. Compared with the baseline (API in 2006), the API rate ratio was only 0.05(95 %CI, 0.04–0.05) in 2013, which equates to a reduction of the malaria burden by 95.0 %. Meanwhile, the health service system was strengthened and health inequity of marginalized populations reduced along the international border. Conclusion The effective collaboration between China, Myanmar and the international non-governmental organization promptly carried out the core interventions through simplified processes. The integrated approaches dramatically decreased malaria burden of Chinese-Myanmar border.